(3TYH GdEjeGfs - (3YHO GdLdjd Hf ehSi Hf YHO GdLdjd GdCfUGQj GdChSj GdbQWHj CHh eMeO GdbUQj,J (B608 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hfeLOg ceG jLH dg Ydi cQe hLhOg s
(3BNQgG (B:s
(3ced cJGH TYH GdEjeGf HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B276 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B83s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(94) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs